2013
DOI: 10.1590/s1516-31802013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia due to Staphylococcus cohnii ssp. urealyticus caused by infected pressure ulcer: case report and review of the literature

Abstract: CONTEXT: Coagulase-negative staphylococci are common colonizers of the human skin and have become increasingly recognized as agents of clinically significant nosocomial infections. CASE REPORT: The case of a 79-year-old male patient with multi-infarct dementia who presented systemic inflammatory response syndrome is reported. This was attributed to bacteremia due to Staphylococcus cohnii ssp. urealyticus, which was grown on blood cultures originating from an infected pressure ulcer. The few cases of Staphyloco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 9 publications
0
31
0
2
Order By: Relevance
“…Recently, more cases of Staphylococcus cohnii infection have been reported in the literature. This organism may be responsible for brain abscess, pneumonia, acute cholecystitis, endocarditis, bacteremia, urinary tract infection and septic arthritis [2]. S.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more cases of Staphylococcus cohnii infection have been reported in the literature. This organism may be responsible for brain abscess, pneumonia, acute cholecystitis, endocarditis, bacteremia, urinary tract infection and septic arthritis [2]. S.…”
Section: Introductionmentioning
confidence: 99%
“…cohnii is a Gram-positive coccus, coagulase negative and catalase positive, that behaves like a commensal mucocutaneous bacterium [4]. It has more frequently been isolated in hospital than in non-hospital environments [2]. Here we report this draft genome of S.…”
Section: Introductionmentioning
confidence: 99%
“…Of all known pathogenic Vibrio of major medical interest listed by Daniels and Shafaie (2000), only V. parahaemolyticus was present in our oyster samples. Among those isolated from surface waters, the coagulase-negative Staphylococcus warneri and S. cohnii are of mild clinical interest as possible sources of nosocomial infections (Martínez and Máttar 2006, Fariña et al 2013, Soldera et al 2013, while Lysobacter spongiicola pertains to a genus of potential importance for its production of several extracellular enzymes (de Bruijn et al 2015), and because several Lysobacter species have been suggested for biological plant disease control (Hashizume et al 2004, Li et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…urealyticus, and Serratia. 4,5 In the long-term catheterization setting, common uropathogens include E. coli, Pseudomonas aeruginosa, and Proteus mirabilis. 4 CAUTI often leads to the development of a biofilm on the long-term indwelling urethral catheter, which can shield the bacteria from antibiotics and promote further bacterial adhesion.…”
Section: Introductionmentioning
confidence: 99%